The Three Musketeers - Dumas, Alexandre; Retold by Cameron, Joan; Illustrated by Humphris, Frank (England Ladybird Books)
Three great swordsmen, Porthos, Aramis, and Anthos, with their protege, D'Artagnan, match wits with the sinister Cardinal Richelieu who seeks to divide the royalty in his own quest for power.
Include Color Illustrations
Keywords: France -- Swordplay -- French fiction